The challenge of HIV treatment in an era of polypharmacy. Issue 2 (3rd February 2020) - Back, David; Marzolini, Catia
Abstract: Introduction: The availability of potent antiretroviral therapy has transformed HIV infection into a chronic disease such that people living with HIV (PLWH) have a near normal life expectancy. However, there are continuing challenges in managing HIV infection, particularly in older patients, who often experience age‐related comorbidities resulting in complex polypharmacy and an increased risk for drug‐drug interactions. Furthermore, age‐related physiological changes may affect the pharmacokinetics and pharmacodynamics of both antiretrovirals and comedications thereby predisposing elderly to adverse drug reactions. This review provides an overview of the therapeutic challenges when treating elderly PLWH (i.e. >65 years). Particular emphasis is placed on drug‐drug interactions and other common prescribing issues (i.e. inappropriate drug use, prescribing cascade, drug‐disease interaction) encountered in elderly PLWH. Discussion: Prescribing issues are common in elderly PLWH due to the presence of age‐related comorbidities, organ dysfunction and physiological changes leading to a higher risk for drug‐drug interactions, drugs dosage errors and inappropriate drug use. Conclusions: The high prevalence of prescribing issues in elderly PLWH highlights the need for ongoing education on prescribing principles and the optimal management of individual patients. The knowledge of adverse health outcomes associated with polypharmacy and inappropriate prescribing should ensure that there are interventions to prevent harm including medication reconciliation, medication review and medication prioritization according to the risks/benefits for each patient.